Respuesta :
To factor this equation out, the easiest way is to solve for the two x values that add up to -1 but when multiplied is equal to -6. It should look like this: (x +- ?)(x +- ?).
The factored out form is then (x - 3)(x +2), because -3 + 2 = -1 and when multiplied together gives -6.
x - 3 = 0
x = 3
x + 2 = 0
x = -2
The two solutions are therefore, x = 3 and x = -2.
The factored out form is then (x - 3)(x +2), because -3 + 2 = -1 and when multiplied together gives -6.
x - 3 = 0
x = 3
x + 2 = 0
x = -2
The two solutions are therefore, x = 3 and x = -2.
Answer:
Option 2 and 5.
The solution of the equation is x=-2 and x=3.
Step-by-step explanation:
Given : Equation [tex]x^2-x-6=0[/tex]
To find : What are the solutions to the equation? Check all that apply.
Solution :
Equation [tex]x^2-x-6=0[/tex]
Substitute all values from options which satisfy the equation is the solution.
1) x=-3
[tex](-3)^2-(-3)-6=0[/tex]
[tex]9+3-6=0[/tex]
[tex]12-6=0[/tex]
[tex]6\neq 0[/tex]
2) x=-2
[tex](-2)^2-(-2)-6=0[/tex]
[tex]4+2-6=0[/tex]
[tex]6-6=0[/tex]
[tex]0= 0[/tex]
3) x=0
[tex](0)^2-(0)-6=0[/tex]
[tex]0-0-6=0[/tex]
[tex]-6\neq 0[/tex]
4) x=2
[tex](2)^2-(2)-6=0[/tex]
[tex]4-2-6=0[/tex]
[tex]-4\neq 0[/tex]
5) x=3
[tex](3)^2-(3)-6=0[/tex]
[tex]9-3-6=0[/tex]
[tex]0=0[/tex]
The solution of the equation is x=-2 and x=3.